2014
DOI: 10.1016/j.ypmed.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional association between mental health and physical activity in older adults: Whitehall II prospective cohort study

Abstract: From midlife to old age, greater physical activity is associated with better mental health and vice versa. These findings suggest persistent longitudinal and bidirectional associations between physical activity and mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 27 publications
3
61
0
3
Order By: Relevance
“…Nevertheless, this does not mean that increased physical activity does not contribute to improved neighbourhood perceptions – these factors may reinforce each other. In fact, multiple studies have provided evidence for a bidirectional relationship between physical activity and mental well‐being . Therefore, the results of the present study may provide a first indication that improvements in neighbourhood attraction, safety and design contribute to neighbourhood perceptions.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Nevertheless, this does not mean that increased physical activity does not contribute to improved neighbourhood perceptions – these factors may reinforce each other. In fact, multiple studies have provided evidence for a bidirectional relationship between physical activity and mental well‐being . Therefore, the results of the present study may provide a first indication that improvements in neighbourhood attraction, safety and design contribute to neighbourhood perceptions.…”
Section: Discussionsupporting
confidence: 55%
“…obesity reviews (2016) 17 (Suppl. 1), [42][43][44][45][46][47][48][49][50][51][52] Introduction Individuals living in socioeconomically deprived neighbourhoods have increased propensity to be overweight, experience poorer health and have higher mortality rates (1)(2)(3). Socioeconomic inequalities may at least be partly related to perceptions of residents in deprived neighbourhoods that their neighbourhood is not conducive to healthy behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…The focus in these studies has usually been the path from LTPA to mental well-being to the relative neglect of the possible reverse causality from mental well-being to LTPA. As an exception, Steinmo et al (2014) in their ten-year follow-up study of middle-aged men and women revealed bidirectional longitudinal associations between LTPA and mental wellbeing. However, while participation in LTPA has generally been shown to predict better subjective health (Holstila et al 2017;Sargent-Cox et al 2014), the reverse, i.e., that subjective health predicts participation in LTPA, has also been reported (Weiss et al 2007).…”
Section: Leisure Time Physical Activity and Well-beingmentioning
confidence: 93%
“…Empirical evidence supports this hypothesis. For instance, cohort studies have indicated bidirectional associations between mental health and physical activity (73) and mental health and noise annoyance (74). If such reciprocal effects exist and occur simultaneously (e.g., mental health and physical activity changing together over time), then longitudinal mediation modelling may fail to capture an indirect effect because of inadequate choice of time lag between the two waves of data collection (75,76).…”
Section: Iqr -Interquartile Range; Sd -Standard Deviationmentioning
confidence: 99%